Karakteristik dan Pemenuhan CPPOB Pelaku UMKM Online Produk Olahan Beku Daging Sapi dan Ayam di DKI Jakarta - Pritanova P, R.; Muhandri, T.; Nurjanah, S. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
Online trading system impacts small and medium entreprsises (SMEs) to easily sell food products andmake the sales of processed food and beverage product in Indonesia continues to grow, however theirawareness to implement food safety standards is still considered as low. This research was aimed todetermine the characteristic and Good Manufacturing Practices (GMP) fulfillment of online SMEswith frozen processed beef and chicken products that is included in medium risk registration categorieswith BPOM MD authorization. Research methods include sample selection of 24 SMEs respondentsin DKI Jakarta with snowball sampling method, questionnaire distribution, field observations anddata processing using descriptive analysis. Analysis of GMP fulfillment by MSMEs is based on eightrequirements refer to Ministry of Industry Regulation Number 75/M-IND/PER/7/2010 concerning GMPguidelines. Results showed that 41.7% the leader had bachelor degree and 54.2% total assets under5 million rupiah with annual turnover under 50 million rupiah. Most of them had IUMK (62.5%),production room located in household kitchen (54.2%) and selling online through social media (95.8%).79.2% of respondents slightly understand about GMP and food safety concept. The most uncompliedfrom eight requirements of GMP was application of lamp protectors in the production room (91.7%).